Development of Argumentative Learning Model Procedures Inquiry Blended Learning on Acid-Base Materials - Feronica Purba; Harizon Harizon; Muhammad Haris Effendi (Universitas Lampung, 2021)
Argumentation skills play a major role in developing critical thinking skills and understanding problems and ideas. Argumentation ability is one of the most complex thinking skills in the learning process. The purpose of this study was to determine the procedure for developing an argumentative inquiry blended learning model on acid-base material. The research method used the